Sistem Pendukung Keputusan menggunakan Metode SMARTER pada Pemilihan Guru Terbaik di SMP Swasta Darularafah Raya - Rika Hanifah Tanjung; Nursakila Ena Anjani; Sofiah Aini; Khairunnisa Ani Putri (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
The internship program is designed to introduce students to the practical application of the theories and knowledge they have acquired during their studies in a real work environment. This activity was conducted at SMP Swasta Galih Agung, an educational institution under the Darularafah Raya Islamic Boarding School Foundation, which aims to develop pious, skilled, and technologically literate students with strong physical and intellectual abilities. At the beginning of the odd semester of the 2023–2024 academic year, the number of female students enrolled was 470, but by the end of the semester, it had decreased to 455, representing a 0.96% decline. The purpose of this study is to perform a ranking analysis for selecting the best teacher based on expertise and teaching performance. The research employs the SMARTER (Simple Multi-Attribute Rating Technique Exploiting Ranks) method, combined with ROC (Rank Order Centroid) weighting and sensitivity analysis to measure the accuracy of ranking results. The findings show that the teacher with code T10 achieved the highest score of 0.521, followed by T7, T1, T2, T5, T11, T12, T8, T4, T9, T6, and T3, with the lowest score being 0.310. The lowest sensitivity value of 0 indicates the most optimal weighting result. The decision support system designed using questionnaires and Excel simplifies data input and assists the principal in making objective and efficient decisions.